Model Hidrologi Produksi Air Bulanan Bagian II: Analisis Korelasi Antara Parameter Model dan Karakteristik Das - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSRTACT An automatic parameter optimization routine was presented. Eleven small watersheds (less than 1000 square krn) in Central Java were used for calibration. A method for estimating four parameters water yield model was obtained Equations for predicting the parameters were developed on the correlation analysis between model p arameters and measurable watershed characteristics.